Тhe concept of constitutionalism and its transformation in the conditions of war - Oleh Martseliak; Svitlana Martseliak; Mykola Martseliak (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2023)
Entry. Constitutionalism belongs to those fundamental legal values ​​that have a complex and multifaceted legal nature, which puts on the agenda a wide range of praxeological challenges regarding the understanding of its phenomenology, the determination of new directions of its development in Ukraine in the conditions of war with the Russian aggressor.